2008
DOI: 10.1093/hmg/ddn167
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus monkeys and humans share common susceptibility genes for age-related macular disease

Abstract: Age-related macular degeneration (AMD), a complex multigenic disorder and the most common cause of vision loss in the elderly, is associated with polymorphisms in the LOC387715/ARMS2 and HTRA1 genes on 10q26. Like humans, macaque monkeys possess a macula and develop age-related macular pathologies including drusen, the phenotypic hallmark of AMD. We genotyped a cohort of 137 unrelated rhesus macaques with and without macular drusen. As in humans, one variant within LOC387715/ARMS2 and one in HTRA1 were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 14 publications
0
77
0
Order By: Relevance
“…This includes 18 loss-of-function and other variants in MYO7A and ABCA4 that affect codons known to cause disease when altered in humans (Molday et al 2009;Millán et al 2011). These codon-specific mutations are particularly valuable in rhesus macaques because this species models human retinal disease more closely than rodent models (Lillo et al 2003;Coleman et al 2004;Francis et al 2008;Colella et al 2013). Across a variety of physiological systems, human genetic mechanisms can be modeled more effectively in primates than in other species (Barr et al 2004;Loffredo et al 2007;Vallender et al 2010;Rogers et al 2013;Phillips et al 2014); thus, functional variants in macaque genes orthologous to human disease genes (eye diseases or others) will provide significant and unique opportunities to model genetic mechanisms or test therapies for those disorders.…”
Section: Functional Annotation Of Rhesus Snvsmentioning
confidence: 99%
“…This includes 18 loss-of-function and other variants in MYO7A and ABCA4 that affect codons known to cause disease when altered in humans (Molday et al 2009;Millán et al 2011). These codon-specific mutations are particularly valuable in rhesus macaques because this species models human retinal disease more closely than rodent models (Lillo et al 2003;Coleman et al 2004;Francis et al 2008;Colella et al 2013). Across a variety of physiological systems, human genetic mechanisms can be modeled more effectively in primates than in other species (Barr et al 2004;Loffredo et al 2007;Vallender et al 2010;Rogers et al 2013;Phillips et al 2014); thus, functional variants in macaque genes orthologous to human disease genes (eye diseases or others) will provide significant and unique opportunities to model genetic mechanisms or test therapies for those disorders.…”
Section: Functional Annotation Of Rhesus Snvsmentioning
confidence: 99%
“…A variety of biochemical, physiological, and genetic studies have been performed on these animals, but the underlying disease mechanism has not yet been identified. However, in rhesus macaques (Macaca mulatta), a recent study reported an association of a HTRA1 polymorphism with formation of drusen (77), while a second study reported a potential AMD-associated polymorphism in LOC387715 and another in HTRA1 (78). Table 1 summarizes the features of AMD that are found in the purported animal models of this disease covered in the above section.…”
Section: Mouse Model For Amd Based On a Deficiency In Factor Hmentioning
confidence: 99%
“…This provides the rationale for current biomedical investigations in which the mechanisms of aging are conducted concurrently in ge-netically robust species like worms, fruit flies, and mice. The use of highly advanced species phylogenetically close to humans, such as rhesus monkeys and chimpanzees, may unveil mechanisms of physiological and cognitive aging that might be more specific to primates (Hoffman and McNaughton, 2002;Peters, 2002;Herbig et al, 2006;Francis et al, 2008). In contrast, small and prolific invertebrates, such as Caenorhabditis elegans (C. elegans) and Drosophila melanogaster, can provide the basis for unbiased screens that identify and determine the precise functions of novel genes that regulate aging and lifespan throughout more levels of evolution.…”
Section: Introductionmentioning
confidence: 99%